2018
DOI: 10.1093/ageing/afy091
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of proactive and multidisciplinary integrated care for older people with complex problems in general practice: an individual participant data meta-analysis

Abstract: Purposeto support older people with several healthcare needs in sustaining adequate functioning and independence, more proactive approaches are needed. This purpose of this study is to summarise the (cost-) effectiveness of proactive, multidisciplinary, integrated care programmes for older people in Dutch primary care.Methods designindividual patient data (IPD) meta-analysis of eight clinically controlled trials.Settingprimary care sector.Interventionscombination of (i) identification of older people with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…GPs are considered to be key actors in the implementation of promising initiatives targeting frail older persons [9]. Many integrated care initiatives have emerged and are implemented in the primary healthcare sector, but evidence of their effectiveness and cost-effectiveness remains mixed [3, 1621]. Integrated primary care programs for frail older persons have shown no effect on the majority of outcomes, and evidence for their cost-effectiveness is limited [16].…”
Section: Introductionmentioning
confidence: 99%
“…GPs are considered to be key actors in the implementation of promising initiatives targeting frail older persons [9]. Many integrated care initiatives have emerged and are implemented in the primary healthcare sector, but evidence of their effectiveness and cost-effectiveness remains mixed [3, 1621]. Integrated primary care programs for frail older persons have shown no effect on the majority of outcomes, and evidence for their cost-effectiveness is limited [16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that patient participation is high on the public agenda, studies show that multidisciplinary teams often operate from a professional perspective, and studies into interprofessional collaboration mainly focus on the viewpoints of professionals [11][12][13] or on more quantitative patient outcomes [14][15][16][17]. Furthermore, as previous studies have stressed, increasing communication with informal caregivers is very important in order to actively involve them in the care of older patients with multimorbidities and complex care needs [18][19][20].…”
Section: Introduction Contextmentioning
confidence: 99%
“…These outpatient assessment programs have been extensively researched, however studies have shown inconsistent effects on clinical outcomes [3] and scarcely any effects on functional dependency [7]. This inconsistency in findings can be explained through the heterogeneity of these multi-component programs [8].…”
Section: Introductionmentioning
confidence: 99%